2013
DOI: 10.2478/s13382-013-0079-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of chromosome damage and promoter methylation status of the DNA repair genes MGMT and hMLH1 in Chinese vinyl chloride monomer (VCM)-exposed workers

et al.

Abstract: Objective: To explore the association of the methylation status of MGMT and hMLH1 with chromosome damage induced by vinyl chloride monomer (VCM). Materials and Methods: Methylation of MGMT and hMLH1 was measured in 101 VCM-exposed workers by methylation-specific PCR. Chromosome damage in peripheral blood lymphocytes was measured by the cytokinesis-block micronucleus assay. The subjects were divided into chromosome damaged and non-damaged groups based on the normal reference value of micronuclei frequencies det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous studies of methylation levels on the same genes we studied have shown them to be altered in the blood of patients with lung cancer and leukocytes collected from blood-exposed populations to particulate matter [15,18]. A recent study of individuals exposed to arsenic in their water supply found increased DNA methylation levels of MLH1 and CDKN2A genes and decreased the methylation level of the repetitive sequence LINE-1 [17].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies of methylation levels on the same genes we studied have shown them to be altered in the blood of patients with lung cancer and leukocytes collected from blood-exposed populations to particulate matter [15,18]. A recent study of individuals exposed to arsenic in their water supply found increased DNA methylation levels of MLH1 and CDKN2A genes and decreased the methylation level of the repetitive sequence LINE-1 [17].…”
Section: Discussionmentioning
confidence: 88%
“…The methylation levels of the MLH1 gene were found to be significantly higher in individuals exposed to arsenic in their water supply [17]. In another study of MLH1 chromosomal instability, as evaluated by MNs, methylation of the MLH1 promoter region in workers exposed to vinyl chloride (plastic) was analyzed [18]. The authors found that methylation of the MLH1 gene was not significantly altered in exposed individuals, but there was increased chromosomal damage as determined by MNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, three types of adipocytes, white, brown, and beige or brite adipocytes, have been identified 4 . Among them, white adipocytes store excess energy in lipid droplets 5 , while beige and brown adipocytes burn lipids to produce heat, thus counteracting obesity 6 , 7 . Unlike white adipocytes, beige and classical brown adipocytes are characterized by their unique ability to transform mitochondrial energy into heat via uncoupling protein 1 (UCP1) 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the elevated promoter methylation in cancer tissues, but to the best of our knowledge, none has reported the methylation status of two genes in benzene-exposed workers. Psofaki et al [45] found that MGMT presented a statistically significant increase in promoter methylation between the less- and more-tumorigenic forms of colorectal adenomas (tubular vs tubullovillous and villous adenomas), and Wu et al [48] previously observed in our lab that MGMT promoter methylation was elevated in vinyl chloride monomer-induced chromosome-damaged subjects. However, Duan et al [9] observed a PAH-related decrease in the methylation of the MGMT promoter, although their in vitro test found that MGMT was methylated in low-dose (2.5 lg/ml) coke oven emissions exposure groups and demethylated in high-dose groups.…”
Section: Discussionmentioning
confidence: 81%